PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM QUIZ TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 20 AMPENAN - Dwi Desi Hariyani Putri; Nurul Kemala Dewi; Awal Nur Kholifatur Rosyidah (PROGRES PENDIDIKAN, 2020)
This study aims to describe the influence of the cooperative learning model team quiz type on the mathematics learning outcomes of fourth-grade students of SD Negeri 20 Ampenan. This type of research is quantitative research. The research method used is Quasi Experiment with research design Nonequivalent Control Group Design. Learning outcomes taken in this study are in three domains, namely cognitive, affective, and psychomotor. The instrument in this study has passed two stages of testing, namely the expert validator test and field testing. The conclusion is drawn by the results of hypothesis testing with pretest and posttest giving questions after being treated with a cooperative learning model type team quiz. Before testing the hypothesis, a prerequisite or parametric test is carried out, namely the Normality Test and the Homogeneity Test. The results of hypothesis testing using the independent sample t-test with the help of SPSS version 16 show the t-count value of 6,979 ≥ t-table 2,021 at a significant level of 5% with df = 67, then Ha is accepted and Ho is rejected, that is, there is an effect on student learning outcomes with the use of cooperative learning model type team quiz. Simple Linear regression test results of 86% with very good interpretation.